Impact of COVID-19 Over Airlines and International Tourism - Gaydarov, Nikola (Research Papers, 2021)
Coronavirus has changed many activities and sectors, but nowhere else are they as accelerated, visible and direct as in the tourism industry. Travel restrictions due to the health crisis have severely damaged tourism, which has made an important contribution to any economy. As of April 2020, the aviation industry reports an 80% decline in flights compared to the same period in 2019. Depending on the duration of the crisis, the considered possibilities show that the potential decline varies between 60-80% in the international tourism economy in 2021. The aim of this study is to examine the negative impact of COVID-19 on airlines and international tourism. A number of universally valid scientific methods are applied in scientific research – observation, analysis, synthesis, analogy, comparison and others. The result of the research is the specific measures for the development of tourism, related to health protocols for safe travel, information applications for visitors, campaigns to promote domestic tourism and a plan to restore tourism in destinations by promoting innovation and investment.